Older Adults’ Pain Descriptions - McDonald, Deborah Dillon (2009)
The purpose of this study was to describe the types of pain information described by older adults with chronic osteoarthritis pain. Pain descriptions were obtained from older adults’ who participated in a posttest only double blind study testing how the phrasing of healthcare practitioners’ pain questions affected the amount of communicated pain information. The 207 community dwelling older adults were randomized to respond to either the open-ended or closed-ended pain question. They viewed and orally responded to a computer displayed videotape of a practitioner asking them the respective pain question. All then viewed and responded to the general follow up question, ““What else can you tell me?” and lastly, “What else can you tell me about your pain, aches, soreness or discomfort?” Audio-taped responses were transcribed and content analyzed by trained, independent raters using 16 a priori criteria from the American Pain Society (2002) Guidelines for the Management of Pain in Osteoarthritis, Rheumatoid Arthritis, and Juvenile Chronic Arthritis. Older adults described important but limited types of information primarily about pain location, timing, and intensity. Pain treatment information was elicited after repeated questioning. Therefore, practitioners need to follow up older adults’ initial pain descriptions with pain questions that promote a more complete pain management discussion. Routine use of a multidimensional pain assessment instrument that measures information such as functional interference, current pain treatments, treatment effects, and side effects would be one way of insuring a more complete pain management discussion with older adults.